ANALISIS DEFORMASI GEMPA PALU 2018 BERDASARKAN PENGAMATAN GPS KONTINU METODE STATIK - Faizal Muttaqin, Muhammad
Sulawesi Island is located within the three tectonic plates, namely the Australian plate, the Philippine plate, and the Sunda plate, known as the triple junction. As a result of the plate activity, one of the faults is the Palu-Koro fault with a velocity of 41-45 millimeters per year. Various earthquake events occurred because of the activity of this fault. One of the biggest was the Palu earthquake on September 28, 2018 with magnitude 7.5 and caused many casualties and losses. Therefore, an understanding of the tectonic conditions of a region is needed due to the event of a disaster. One of them is GPS observation to determine the deformation pattern that it can be used in disaster mitigation efforts. The method of this research is done by processing GPS rinex data from CORS BIG and IGS using Bernese 5.2 software. The results of this processing are time series, displacement vectors, and velocity vectors due to earthquakes. The result is a horizontal position change due to the Palu earthquake September 28, 2018. The magnitude of the vector displacement from the observation point of the station due to the earthquake has a range from 1.4 mm to 25.53 mm. Directions of all stations, to the northward is dominant in northern Sulawesi and southward is dominant in southern Sulawesi. This occurred because of the coseismic effect of the earthquake as a result of the Palu Koro fault movement which is a left-lateral strike-slip fault trending north-south direction. The velocity vector before the earthquake ranged from 0.0039 m/yr to 0.0259 m/yr. While the velocity vector after the earthquake ranged from 0.0039 m/yr to 0.0938 m/th. The displacement velocity residue due to the earthquake ranged from 0.0047 m/yr to 0.0961 m/yr. This residue indicates a postseismic effect from the earthquake that produces a deformation pattern.